On the Security of the Stream Ciphers RCR-64 and RCR-32. (13th September 2021) - Joseph, Mabin; Sekar, Gautham; Balasubramanian, R; Venkiteswaran, G
Abstract: The stream ciphers RCR-64 and RCR-32 designed by Sekar et al. are the most recent additions to the Py-family of stream ciphers, originally designed by Biham et al. The ciphers are among the fastest stream ciphers on software. To the best of our knowledge, the only reported attacks on the ciphers are due to Ding et al., published in the Journal of Universal Computer Science . In this paper, we review these alleged attacks on the RCR ciphers and show that they are based on non-existent keystream biases stemming from flawed probability calculations.